Novirin Effectiveness in Children with Viral Diarrhea - S.O. Kramariov; V.V. Yevtushenko; O.M. Yevtushenko; Ye.A. Maievska; V.V. Babak (Zaslavsky O.Yu., 2015)
The article deals with the issues of treatment for viral diarrhea. The main direction in the treatment of acute viral intestinal infections is the use of rehydration and drugs for symptomatic therapy. Also, research data repeatedly confirmed the effectiveness of antiviral agents. In recent years, inosine pranobex, an antiviral agent with immunomodulating properties, is being successfully used for the treatment of viral diseases in children. In the present study, the authors demonstrated the effectiveness of Novirin (inosine pranobex) in the treatment of viral diarrhea in children: administration of Novirin made it possiblee to stop diarrhea in the first 5 days after treatment initiation in significantlylarger number of children (80 %) compared with the control group (43 %).